Chromosomal instability and phenotypic variation in a specific lineage derived from a synthetic allotetraploid wheat - Lv, Ruili; Wang, Changyi; Wang, Ruisi; Wang, Xiaofei; Zhao, Jing; Wang, Bin; Aslam, Tariq; Han, Fangpu; Liu, Bao (Frontiers in Plant Science, 2022)
Newly formed plant allopolyploids usually have meiosis defect, resulting in chromosomal instability manifested as variation in chromosome number and/or structure. However, not all nascent allopolyploids are equally unstable. The wheat group (Aegilops/Triticum) contains 13 diploid species with distinct genome types. Many of these species can be artificially hybridized to produce viable but sterile inter-specific/intergeneric F1 hybrids, which can generate fertile synthetic allotetraploid wheats after whole genome doubling. Compared with synthetic allotetraploid wheats that contain genome combinations of AADD and S*S*DD (S* refers to related S genomes of a different species), those containing an S*S*AA genome are significantly more stable. However, robustness of the relative stability of S*S*AA genomes is unknown, nor are the phenotypic and fitness consequences during occurrences of secondary chromosomal instability. Here, we report a specific lineage originated from a single individual plant of a relatively stable synthetic allotetraploid wheat with genomes SlSlAA (Sl and A subgenomes were from Ae. longissima and T. urartu, respectively) that showed a high degree of transgenerational chromosomal instability. Both numerical chromosome variation (NCV) and structural chromosome variation (SCV) occurred widely. While substantial differences in frequencies of both NCV and SCV were detected across the different chromosomes, only NCV frequencies were significantly different between the two subgenomes. We found that NCVs and SCVs occurred primarily due to perturbed meiosis, allowing formation of multivalents and univalents as well as homoeologous exchanges. Thus, the combination of NCVs and SCVs affected multiple phenotypic traits, particularly those related to reproductive fitness.